2019
DOI: 10.2478/helm-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of myeloid and lymphoid cell populations to apoptosis in peritoneal cavity of mice with model larval Mesocestoides vogae infection

Abstract: SummaryThe metacestode stage of the tapeworm Mesocestoides vogae (M. vogae) has the ability of asexual growth in the peritoneal cavity of rodents and other intermediate hosts without restriction. Early immunological events have decisive role in the establishment of infection. In the present study we investigated the kinetic of myeloid and lymphoid cell populations and the proportions of cells undergoing apoptosis in peritoneal cavities of mice within the first month after oral infection with M. vogae larvae. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Moreover, we found that M. vogae infection influenced the expression of F4/80 and MHC II markers on the myeloid peritoneal cell population. Recently, we showed that peritoneal myeloid cells undergo apoptosis in response to M. vogae infection [ 33 ] and that ES products can directly inhibit the activation of antigen presenting cells [ 34 ], which may mediate immunosuppression. The alternation of MHC II and F4/80 expression levels in PEC demonstrates the complex network of interactions and regulatory mechanisms that occur during an experimental infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that M. vogae infection influenced the expression of F4/80 and MHC II markers on the myeloid peritoneal cell population. Recently, we showed that peritoneal myeloid cells undergo apoptosis in response to M. vogae infection [ 33 ] and that ES products can directly inhibit the activation of antigen presenting cells [ 34 ], which may mediate immunosuppression. The alternation of MHC II and F4/80 expression levels in PEC demonstrates the complex network of interactions and regulatory mechanisms that occur during an experimental infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that M. vogae infection in uenced the expression of F4/80 and MHC II markers on the myeloid peritoneal cell population. Recently, we showed that peritoneal myeloid cells undergo apoptosis in response to M. vogae infection [33] and that ES products can directly inhibit the activation of antigen presenting cells [34], which may mediate immunosuppression. The alternation of MHC II and F4/80 expression levels in PEC demonstrates the complex network of interactions and regulatory mechanisms that occur during an experimental infection.…”
Section: Discussionmentioning
confidence: 99%